A Madison for Outcasts: Dance and Critical Displacements in Jean-Luc Godard’s Band of Outsiders - Becker, Svea; Williams, Bruce (Cinémas)

(untitled) (Cinémas, 2008)
AbstractIn light of Timothy Corrigan’s discussion of the cult film as “adopted child,” Godard’s Band of Outsiders (Bande à part) can be viewed as a film which has transcended its original destiny and opened doors to diverse critical and spectatorial receptions. Drawing upon pulp fiction and the “B movie” genre, Godard’s original intent was to make a mainstream film. But it was precisely the film’s homage to the American mainstream that soon led to its cult status in non-mainstream cinema. Based on a pulp fiction novel by Delores Hitchens, Band of Outsiders celebrates dance and movement from American popular culture and, in particular, American jazz dance as popularized in Europe in the early 1960s. In one sequence, the protagonists break into the Madison, a line dance that quickly moved from the African-American community to the white mainstream through such television shows as American Bandstand and to Europe through the work of such performers/teachers as Harold Nicholas. The freedom of movement within a structured environment, which defines the Madison, recalls the director’s own approach to filmmaking as well as his high regard for the physical dexterity of his actors. Inasmuch as each dancer dances the Madison “solo,” the dance allows individual characters to articulate through movement their mental and emotional states. At the same time, it permits the three protagonists to function as a synchronized group, a “band of outsiders.” The Madison sequence, moreover, presents a microcosm of many of the ideological and aesthetic premises of the Nouvelle Vague and is particularly reflective of Godard’s love of Americana. This dance, itself synonymous with the film, is the sequence that generates the most intricate intertextual references as well as the most divergent critical response. The Madison has thus become the vehicle through which Band of Outsiders has come to stand in for non-mainstream cinema at large.